2020
DOI: 10.1111/jpy.13093
|View full text |Cite
|
Sign up to set email alerts
|

Morphological evolution of silica scales in the freshwater genus Synura (Stramenopiles)

Abstract: A high degree of morphological variability is expressed between the ornately sculptured siliceous scales formed by species in the chrysophycean genus, Synura. In this study, we aimed to uncover the general principles and trends underlying the evolution of scale morphology in this genus. We assessed the relationships among thirty extant Synura species using a robust molecular analysis that included six genes, coupled with morphological characterization of the species‐specific scales. The analysis was further en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 86 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…Smaller elliptical-shaped scales would be more efficient in covering a curving ellipsoidal cell surface than larger and square-shaped scales, and allow for a closer fitting cell covering. Jadrná et al 26 recently reported that scales of the closely related synurophyte genus, Synura , have also become smaller and more elongate over geologic time, complementing the observations for Mallomonas . Taken together, these findings support the idea that the evolutionary trend for synurophyte organisms has been towards smaller, elliptical scales.…”
Section: Discussionmentioning
confidence: 59%
“…Smaller elliptical-shaped scales would be more efficient in covering a curving ellipsoidal cell surface than larger and square-shaped scales, and allow for a closer fitting cell covering. Jadrná et al 26 recently reported that scales of the closely related synurophyte genus, Synura , have also become smaller and more elongate over geologic time, complementing the observations for Mallomonas . Taken together, these findings support the idea that the evolutionary trend for synurophyte organisms has been towards smaller, elliptical scales.…”
Section: Discussionmentioning
confidence: 59%
“…Some of these evolutionary trends in changes in spine complexity and transitions between the two genera were originally suggested by Nicholls (1984), but without knowledge of their phy logeny. Such similar trends in scale ultrastructure and size changes are only partially known for Mallomonas and Synura silica-scaled taxa (Čertnerová et al 2019;Jadrná et al 2021;Siver 2022). Therefore, molecular characterization of other Spiniferomonas and Chrysosphaerella species is very important as it may provide a key to better understanding the evolution of silicascaled chrysophytes and their armour in general.…”
Section: Discussionmentioning
confidence: 96%
“…The scales of Synurales taxa therefore clearly play an important role for their carriers. Many hypotheses have been proposed to explain the potential benefits of a silica cell covering, including conserving resources, increasing light diffraction, reducing dan gerous UV radiation, or impeding grazing, parasitoid or viral attack (Finkel & Kotrc 2010;Jadrná et al 2021 and references herein). Though a mechanical defense against predation is the most mentioned function of silica structures in chrysophytes, the results of laboratory experiments are quite confusing since in some cases predators preferred the scale-covered over naked cells or colonies of the same prey species (Sandgren & Walton 1995).…”
Section: Discussionmentioning
confidence: 99%